Gastric Obstruction by Tricobezoar in Cat Associated with Lynxacarus radovskyi: a Case Report - Arruda , Érico do Nascimento; Marques , Marilene da Silva; Galera , Paula Diniz; Sousa Filho, Reginaldo Pereira de; Monteiro , Cynthia Levi Baratta (Brazilian Journal of Case Reports, 2021)
The presence of trichobezoar in cats is characterized by the accumulation of hair in the gastric cavity, which may be associated with the presence of dermatitis caused by the presence of the mite Lynxacarus radovskyi. In the present report, a clinical case of a feline patient with diagnostic and surgical diagnosis of the presence of a trichobezoar with the presence of Lynxacarus radovskyi in a skin scrape examination was described.